Acoustical source localization in microphone array systems - Jian, Ming (2008)
Acoustical source localization is the first important stage of an intelligent micro-phone array system used for high quality speech pick-up in noisy and reverberant environments. In this thesis, acoustical source localization in microphone arrays is studied.